Hubungan Antara Indeks Massa Tubuh Sebagai Faktor Risiko Diabetes Melitus Tipe 2 Dengan Profil Glukosa Darah dan Tinjauannya Menurut Pandangan Islam - Pratiwi, Gina Marta; Purnamasari, Endah; Maharsi, Eri Dian; Karimulloh, Karimulloh (Syntax Literate, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease with an increasing global prevalence. One of the main risk factors is obesity, which can be assessed using the Body Mass Index (BMI). University students, as part of the productive age group, are vulnerable to increases in BMI and blood glucose levels due to unhealthy lifestyles. Therefore, it is important to investigate the relationship between BMI and blood glucose levels as an early preventive measure against T2DM. This study applied a quantitative analytical observational method with a cross-sectional approach. Data were collected by measuring BMI and examining blood glucose levels, specifically Random Blood Glucose (RBG) and Fasting Blood Glucose (FBG), in 92 students using Point of Care Testing (POCT) devices. Statistical analysis of 92 participants for both RBG and FBG, the results indicated no significant association between BMI and random blood glucose levels (p=0,426) nor between BMI and fasting blood glucose levels (p=0,970). In conclusion, there is no significant relationship between BMI as a risk factor for T2DM and blood glucose levels among medical students at YARSI university.